Development and feasibility of a child obesity prevention intervention in general practice: The Healthy 4 Life pilot study. (19th June 2014) - Denney‐Wilson, Elizabeth; Robinson, Alison; Laws, Rachel; Harris, Mark Fort
<x xml:space="preserve">Abstract</x> Aim Approximately 20% of Australian pre‐school children are overweight. Primary care providers have a crucial role in identifying children at risk of unhealthy weight gain and to offer advice and suggestions to parents. The Healthy 4 Life pilot study aimed to develop and test the feasibility of a practice nurse (PN)‐led brief intervention into a healthy kid's check in general practice. Methods A PN intervention was developed based on a needs assessment and existing literature. A workshop was conducted, and resources were provided to enable four PNs to deliver a brief obesity prevention intervention to parents. Nurses then incorporated the Healthy 4 Life components into the healthy kid's checks they conducted on the next 10 children. Medical records were reviewed and nurses interviewed to establish the feasibility of the intervention. Results All of the nurses incorporated some Healthy 4 Life components into their healthy kid's checks. Body mass index was calculated and plotted for all children, and advice around healthy eating was offered in 60% of consultations; however, advice about limiting screen time provided in only 2% of consultations. Nurses reported that the intervention fitted well with their current practice, although time constraints were a concern for some nurses and some parents. Conclusion The provision of a brief training workshop and resources can equip nurses in general practice to offer an obesity prevention intervention to parents of young children. Further research is required to examine the impact of such an intervention on parent and child behaviours and the sustainability of such practices for PNs.